A2 8 From Sandworms to Saplings: Cooling Arrakis with Trees - Dyer, Thomas; Lewis, Dan; Scrivener, Callum (Physics Special Topics, 2024)
In this paper, we investigate the feasibility of terraforming Arrakis through planting trees like how it is done in the Dune Franchise. We have determined that due to the change in albedo, despite the evapotranspirational effect, the temperature of the planet would increase to approximately 325 °C, proving that other methods of terraforming were undertaken but not described.